Epoxy resin-based adhesive as well as preparation method and application thereof
By adding reinforcing materials and coupling agents to the epoxy resin adhesive and using ultrasonic treatment and vacuum curing technology, the problems of poor weather resistance, aging resistance and mechanical properties of existing epoxy resin adhesives in fiberglass pipe repair are solved, and the preparation of excellent adhesives is achieved, meeting the needs of rapid on-site repair of oil fields.
Patent Information
- Application Number
- CN202311436657.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-31
- Publication Date
- 2025-05-02
AI Technical Summary
The existing epoxy resin adhesives have poor weather resistance, aging resistance and mechanical properties (especially impact strength) in the repair of fiberglass pipes, resulting in long maintenance cycles, complex construction processes and unfriendly to the environment, making it difficult to meet the requirements of rapid emergency repairs on the oil field.
Hydrogenated bisphenol A type epoxy resin is used as the matrix, and reinforcing materials (such as magnesium-aluminum carbonate layered bimetallic hydroxide Mg/Al-LDHs), coupling agents (such as γ-(2,3-epoxypropoxy)propyltrimethoxysilane KH-560) and accelerators (such as benzyldimethylamine or 1,8-diazabicycloundec-7-ene) are added, and epoxy resin-based adhesives with excellent performance are prepared through sonication and vacuum curing technology.
It improves the mechanical properties of epoxy resin-based adhesives, enhances their weather resistance and aging resistance, and meets the needs of rapid on-site repairs of oil fields. At the same time, it is simple in process, environmentally friendly, and cost-saving.
Smart Images

Figure CN119912888A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adhesive preparation, and specifically relates to an epoxy resin-based adhesive and a preparation method and application thereof. Background Art
[0002] At present, the most widely used pipes in domestic oilfield surface gathering and transportation systems are carbon steel and low alloy steel. However, in recent years, as the oilfield medium environment has become increasingly harsh, the water content and temperature have gradually increased, and the content of corrosive media such as Cl- and CO2 has increased. Even H2S has appeared in oil and gas wells in some areas (such as Sichuan, Chongqing, Tarim, etc.), which has brought great risks to the application of steel pipes. FRP refers to a composite material formed by adding glass fiber reinforced materials to thermosetting resins (epoxy resins, unsaturated polyester resins, etc.) or wrapping them. It has excellent corrosion resistance and anti-scaling and waxing properties. When prepared into FRP pipes in the oil and gas field, they can withstand various corrosive media in the oilfield for a long time, without the need for internal and external corrosion protection, and have a long service life. It has been widely promoted and applied on site in oilfields. When FRP pipes are damaged or ruptured during their use, adhesives are often used for repair. However, the commonly used epoxy resin adhesives currently have problems such as poor weather resistance, high production costs, aging resistance, and poor impact resistance. When used to repair FRP pipes, the maintenance cycle is long, the construction process is complex, and it is not environmentally friendly, making it difficult to meet the requirements for rapid emergency repairs on site in oil fields. Summary of the invention
[0003] The purpose of the present invention is to provide an epoxy resin-based adhesive and a preparation method and application thereof, which solves the problem that the existing adhesive has poor weather resistance, aging resistance and mechanical properties (especially impact strength).
[0004] The present invention is achieved through the following technical solutions:
[0005] The present invention discloses an epoxy resin-based adhesive, which comprises the following components in parts by mass:
[0006] 1 part of hydrogenated bisphenol A epoxy resin, 0.01-0.07 parts of reinforcing material, 0.02-0.07 parts of coupling agent, 0.35-0.51 parts of curing agent, and 0.01-0.06 parts of accelerator.
[0007] Furthermore, the curing agent is polyetheramine D-230, T-403 or MeTHPA.
[0008] Furthermore, the accelerator is benzyldimethylamine or 1,8-diazabicycloundec-7-ene.
[0009] Furthermore, the reinforcing material is magnesium aluminum carbonate type layered double hydroxide Mg / Al-LDHs.
[0010] Furthermore, the coupling agent is γ-(2,3-epoxypropoxy)propyltrimethoxysilane KH-560.
[0011] The present invention also discloses a method for preparing the epoxy resin-based adhesive, comprising the following steps:
[0012] (1) mixing the dried hydrogenated bisphenol A epoxy resin with a reinforcing material, a coupling agent, etc. in a uniform ratio to obtain a component A;
[0013] (2) dispersing component A, then mixing it evenly with a curing agent and an accelerator, ultrasonically treating it, and then vacuuming it to obtain a hydrogenated bisphenol A epoxy resin matrix;
[0014] (3) dispersing a hydrogenated bisphenol A epoxy resin matrix, performing ultrasonic treatment, vacuum drying, evacuating, and curing to obtain an epoxy resin-based adhesive.
[0015] Furthermore, in step (2), the dispersion is carried out for 5-10 minutes and the ultrasonic treatment is carried out for 15-30 minutes.
[0016] Furthermore, in step (2), vacuum is applied at 0.01 MPa.
[0017] Furthermore, in step (3), the dispersion is carried out for 5-10 minutes and the ultrasonic treatment is carried out for 15-30 minutes.
[0018] The invention also discloses the use of the epoxy resin-based adhesive as a repairing agent in repairing glass fiber reinforced plastic pipes.
[0019] Compared with the prior art, the present invention has the following beneficial technical effects:
[0020] The invention discloses an epoxy resin-based adhesive, comprising hydrogenated bisphenol A epoxy resin, a reinforcing material, a coupling agent, a curing agent and an accelerator. The hydrogenated bisphenol A epoxy resin has no rigid groups and has certain flexibility and toughness. The reinforcing material and the coupling agent are added in the process to improve the mechanical properties. The hydrogenated bisphenol A epoxy resin can effectively overcome the problem that the bisphenol A epoxy resin has an unsaturated benzene ring structure in its structure, which causes aging and discoloration under long-term ultraviolet light irradiation, resulting in poor weather resistance and ultraviolet resistance, and greatly reduced various properties.
[0021] Silane coupling agent overcomes the defect of uneven dispersion of reinforcing materials in epoxy resin / curing agent system and improves the bonding performance of epoxy adhesive. In this system, chemical and physical bonding occurs between reinforcing materials and epoxy resin. First, the bonding between Mg / Al-LDHs and resin improves the strength of the matrix; second, the reinforcing materials can be distributed in the gaps formed by polymer bonds to form a network structure and enhance performance.
[0022] Epoxy resin and curing agent will form chemical bonds in the reaction to form a three-dimensional network structure. This structure determines the hardness, strength, heat resistance and other properties of the material. If the curing agent ratio is too high, the material will be too hardened and lose toughness; if the curing agent ratio is too low, the material will soften and lose strength and heat resistance; the proportion of the accelerator will also affect the reaction process. The accelerator can accelerate the chemical reaction and increase the reaction rate and reaction degree; in the reaction of epoxy resin and curing agent, the accelerator can increase the rate of curing reaction and make the reaction proceed faster; if the accelerator ratio is too high, the reaction will be too fast and the material cannot be fully cured; if the accelerator ratio is too low, the reaction will be too slow and the material cannot be cured in time. Therefore, the ratio of epoxy resin, curing agent and accelerator needs to be adjusted according to the specific application requirements to achieve the best performance and reaction effect. The epoxy system involved in the present invention is more suitable within this ratio range.
[0023] Furthermore, the coupling agent uses KH-560, which acts as a bridge and contains amphiphilic functional groups. One end of the coupling agent has an epoxy group that can react chemically with the epoxy resin, and the other end has a silanol group that can react chemically with the surface functional groups of the reinforcing material, thereby improving the compatibility between the inorganic network structure of silica and the organic phase epoxy resin, and closely combining the inorganic component with the organic component to achieve a synergistic effect. This can inhibit the agglomeration of the reinforcing material, and enhance the compatibility of the reinforcing material with the resin matrix, so that the reinforcing material is more evenly dispersed in the resin matrix.
[0024] The present invention also discloses a preparation method of the epoxy resin-based adhesive, which can react at room temperature, has a simple preparation process, and mild reaction conditions; compared with other adhesives on the market, it can achieve the purpose of cost saving and can be mass-produced, has no three wastes discharged, and has the characteristics of being environmentally friendly.
[0025] The epoxy resin-based adhesive prepared by the present invention is mainly used for repairing glass fiber reinforced plastic pipes through winding molding or hand lay-up molding. Studies have shown that the composite fiber material made of glass fiber cloth and epoxy resin adhesive can not only effectively prevent the product from being damaged, but also can design the winding law according to the stress condition of the product, so that the strength performance of the fiber can be fully exerted. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The reaction mechanism of epoxy curing with amine curing agents;
[0027] Figure 2 The flow chart of preparing epoxy resin glass cloth by winding molding process;
[0028] Figure 3 is the impact strength of epoxy resin-based adhesives in different systems;
[0029] Figure 4 is the flexural strength of epoxy resin-based adhesives in different systems. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solution and advantages of the present invention more clear, the following is further described in detail with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention, that is, the embodiments described are only part of the embodiments of the present invention, not all embodiments.
[0031] The components described and shown in the drawings and embodiments of the present invention may be arranged and designed in various configurations. Therefore, the detailed description of the embodiments of the present invention provided in the following drawings is not intended to limit the scope of the claimed invention, but merely represents a selected embodiment of the present invention. Based on the drawings and embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0032] It should be noted that the terms "comprises", "includes" or any other variations are intended to cover non-exclusive inclusion, so that a process, element, method, article or equipment that includes a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to the process, element, method, article or equipment.
[0033] The present invention discloses an epoxy resin-based adhesive, which comprises the following components in parts by mass:
[0034] 1 part of hydrogenated bisphenol A epoxy resin, 0.01-0.07 parts of reinforcing material, 0.02-0.07 parts of coupling agent, 0.35-0.51 parts of curing agent, and 0.01-0.06 parts of accelerator.
[0035] The features and performances of the present invention are further described in detail below in conjunction with the embodiments.
[0036] Implementation Case 1
[0037] In step 1 of this implementation case, a resin matrix with HBPA-EP / D-230 as the system is prepared. According to the mass ratio, the system formula includes epoxy resin HBPA-EP, polyether amine D-230, accelerator (BMDA), coupling agent (KH560), and Mg / Al-LDHs=1:0.37:0.04:0.03:0.04.
[0038] This embodiment discloses a method for preparing a glass fiber reinforced epoxy resin-based composite material, comprising the following steps:
[0039] Step 1: Mix 67.5g of dried hydrogenated bisphenol A epoxy resin with 3g of Mg / Al-LDHs and 2g of coupling agent KH560, disperse them for 5min under a high-speed dispersing homogenizer, then add 25g of curing agent D-230 and 2.5g of accelerator BMDA, ultrasonically treat for 15min, and then vacuum treat for a period of time at 0.01MPa to obtain a hydrogenated bisphenol A epoxy resin matrix. See the reaction mechanism diagram for details. Figure 1 .
[0040] Step 2: Mix evenly according to the mixing system determined by the experiment, disperse in a high-speed homogenizer for 5 minutes, and evacuate in a vacuum drying oven after ultrasonic treatment for 15 minutes to prevent the formation of bubbles. Prepare the epoxy resin-based adhesive according to the curing process of 60℃ / 1h+90℃ / 1h+120℃ / 1h.
[0041] Implementation Case 2
[0042] In step 1 of this implementation case, a resin matrix with HBPA-EP / D-230 as the system is prepared. According to the mass ratio, the system formula includes epoxy resin HBPA-EP, polyether amine D-230, accelerator (DBU), coupling agent KH560, and Mg / Al-LDHs=1:0.51:0.05:0.07:0.07.
[0043] This embodiment discloses a method for preparing a glass fiber reinforced epoxy resin-based composite material, comprising the following steps:
[0044] Step 1: Mix 59g of dried hydrogenated bisphenol A epoxy resin, 4g of nano Mg / Al-LDHs, and 4g of coupling agent KH560 in the above proportions, disperse them for 10min under a high-speed dispersing homogenizer, then add 30g of curing agent D-230 and 3g of accelerator DBU, ultrasonically treat for 30min, and then vacuum treat for a period of time at 0.01MPa to obtain a hydrogenated bisphenol A epoxy resin matrix. The reaction mechanism is shown in Figure 1 .
[0045] Step 2: Evenly mix the mixed system prepared in step 1, disperse it in a high-speed homogenizer for 10 minutes, and evacuate the mixture in a vacuum oven after ultrasonic treatment for 30 minutes to prevent the formation of bubbles. Curing at room temperature for 1 day, and post-treatment at 60° C. for 1 hour, to prepare an epoxy resin-based adhesive.
[0046] The bonding strength of this example was tested on a universal testing machine according to GB / T 7124-2008 standard (constant tensile rate, bonding surface size 12*10mm), and the bonding test piece was 45# steel, which was quite different from the bonding strength tested in Example 1. The bonding strength tested under the curing process of 60℃ / 1h+90℃ / 1h+120℃ / 1h was 21.62MPa, and the bonding strength was 27.33MPa after curing at room temperature for 1d and post-treatment at 60℃ for 1h.
[0047] Implementation Case 3
[0048] In step 1 of this implementation case, a resin matrix with HBPA-EP / T-403 as the system is prepared. According to the mass ratio, the system formula includes epoxy resin HBPA-EP, polyether amine T-403, accelerator (DBU), coupling agent (KH560), and Mg / Al-LDHs=1:0.42:0.03:0.05:0.05.
[0049] This embodiment discloses a method for preparing an epoxy resin-based adhesive, comprising the following steps:
[0050] Step 1: Mix 65g of dried hydrogenated bisphenol A epoxy resin, 3g of Mg / Al-LDHs, and 3g of coupling agent KH-560 in the above proportions, disperse for 8 minutes under a high-speed dispersing homogenizer, then add 27g of curing agent T-403 and 2g of accelerator DBU, ultrasonically treat for 20 minutes, and then vacuum treat for a period of time at 0.01MPa to obtain a hydrogenated bisphenol A epoxy resin matrix. The reaction mechanism is shown in Figure 1 .
[0051] Step 2: The mixed system prepared in step 1 is mixed evenly, dispersed in a high-speed homogenizer for 8 minutes, and evacuated in a vacuum drying oven after ultrasonic treatment for 20 minutes to prevent the generation of bubbles. The same curing process as in implementation case 1 is adopted to prepare an epoxy resin-based adhesive.
[0052] Implementation Case 4
[0053] In step 1 of this implementation case, a resin matrix with E-51 / D-230 as the system is prepared. According to the mass ratio, the system formula includes epoxy resin E-51, polyether amine D-230, accelerator (DBU), coupling agent (KH560), and Mg / Al-LDHs=1:0.44:0.04:0.05:0.04.
[0054] This embodiment discloses a method for preparing an epoxy resin-based adhesive, comprising the following steps:
[0055] Step 1: Mix 64g of dried epoxy resin (E-51) with 2.5g of Mg / Al-LDHs and 3g of coupling agent KH-560 in the above proportions, disperse for 9 minutes under a high-speed dispersing homogenizer, then add 28g of curing agent D-230 and 2.5g of accelerator DBU, ultrasonically treat for 28 minutes, and then vacuum treat for a period of time at 0.01MPa to obtain an epoxy resin matrix. The reaction mechanism is shown in Figure 1 .
[0056] Step 2: The mixed system prepared in step 1 was mixed evenly, dispersed in a high-speed homogenizer for 9 minutes, and then vacuumed in a vacuum drying oven after ultrasonic treatment for 28 minutes to prevent the formation of bubbles, and the same curing process as in Example 1 was adopted to prepare an epoxy resin-based adhesive. This example is used as a control example.
[0057] Implementation Case 5
[0058] In step 1 of this implementation case, a resin matrix of the HBPA-EP / MeTHPA system is prepared. According to the mass ratio, the system formula includes epoxy resin HBPA-EP, curing agent MeTHPA, accelerator BMDA, coupling agent (KH560), and Mg / Al-LDHs=1:0.38:0.02:0.04:0.02.
[0059] This embodiment discloses a method for preparing an epoxy resin-based adhesive, comprising the following steps:
[0060] Step 1: 68.5 g of hydrogenated bisphenol A epoxy resin (HBPA-EP) after drying, 1.5 g of Mg / Al-LDHs, and 2.5 g of coupling agent KH-560 were mixed evenly according to the above proportions, dispersed for 6 min under a high-speed dispersing homogenizer, and then 26 g of curing agent MeTHPA and 1.5 g of accelerator BMDA were added, and then ultrasonically treated for 16 min and then vacuumed at 0.01 MPa for a period of time to obtain a hydrogenated bisphenol A epoxy resin matrix. The reaction mechanism is shown in Figure 1 .
[0061] Step 2: Evenly mix the mixed system obtained in step 1, disperse it in a high-speed homogenizer for 6 minutes, and evacuate the mixture in a vacuum drying oven after ultrasonic treatment for 16 minutes to prevent the formation of bubbles. Prepare the epoxy resin-based adhesive at 80°C / 1h+100°C / 0.5h+120°C / 0.5h+140°C / 0.5h+160°C / 0.5h.
[0062] Implementation Case 6
[0063] In step 1 of this implementation case, a resin matrix with E-51 / MeTHPA as the system is prepared. According to the mass ratio, the system formula includes epoxy resin E-51, curing agent MeTHPA, accelerator (BMDA), coupling agent (KH560), and Mg / Al-LDHs=1:0.47:0.04:0.06:0.06.
[0064] This embodiment discloses a method for preparing an epoxy resin-based adhesive, comprising the following steps:
[0065] Step 1: Mix 29g of dried epoxy resin (E-51) with 3.5g of Mg / Al-LDHs and 3.5g of coupling agent KH-560 in the above proportions, disperse for 7min under a high-speed homogenizer, then add 29g of curing agent MeTHPA and 2.5g of accelerator BMDA, ultrasonically treat for 17min, and then vacuum treat for a period of time at 0.01MPa to obtain an epoxy resin matrix. The reaction mechanism is shown in Figure 1 .
[0066] Step 2: Evenly mix the mixed system prepared in step 1, disperse it in a high-speed homogenizer for 7 minutes, and evacuate the mixture in a vacuum drying oven after ultrasonic treatment for 17 minutes to prevent the formation of bubbles. Prepare the epoxy resin-based adhesive at 80°C / 1h+100°C / 0.5h+120°C / 0.5h+140°C / 0.5h+160°C / 0.5h.
[0067] The impact bending strength tests of epoxy resin-based adhesives of different systems described in cases 1, 3, 5, and 6 were carried out. The impact performance tests were carried out on a ZBC-4 pendulum impact tester in accordance with GB / T 2571-2008, and the test results were 61.54MPa, 43.92MPa, 16.51MPa, and 14.47MPa, respectively. The bending performance tests were carried out on a multifunctional testing machine in accordance with GB / T 2570-2008, and the test results were 120.92MPa, 114.79MPa, 141.67MPa, and 131.60MPa, respectively.
[0068] Application Example 1
[0069] Fully immerse the glass cloth in the epoxy resin adhesive, squeeze it so that the glass cloth can be evenly dipped in the adhesive and the bubbles are squeezed out, and then evenly apply the resin again. Repeat the above process until the thickness reaches about 4mm to obtain the epoxy resin glass cloth;
[0070] After that, the epoxy resin glass cloth is wound around the core mold according to a certain rule, and the mold is solidified and demoulded to obtain a composite product, namely a glass fiber reinforced plastic pipe. The heating temperature range is 120℃, and the molding process flow chart is shown in Figure 2 shown.
[0071] The bending performance of the test application example 1 was tested on a multifunctional testing machine according to GB / T 2570-2008, and the bending strength reached 1772.4MPa.
[0072] Application Example 2
[0073] Use hand lay-up molding to clean the surface of the damaged part of the FRP pipe and polish the surrounding area. Apply epoxy resin adhesive evenly around the FRP pipe to be repaired, so that the fiberglass cloth is completely soaked in the epoxy resin adhesive and the position where the repair adhesive is applied is wrapped around the fiberglass cloth along the circumference of the FRP pipe. After wrapping, cure the wrapped area until the epoxy resin adhesive is cured, apply the epoxy resin adhesive again, bake it for the second time until it is cured, and the curing temperature is 80-120℃. Repeat the above operation until the thickness reaches 4mm to complete the repair of the FRP pipe.
[0074] See also Figure 3 , the impact strength of epoxy resin-based adhesives under different systems was analyzed. Since the curing agents D-230 and T-403 are both flexible curing agents, the flexible molecular chains can increase the molecular weight of the crosslinking points and reduce the crosslinking density. The hydrogenated bisphenol A epoxy resin is used as the matrix, which makes the rigid groups less, so the impact strength of these two curing systems is relatively high. The impact strength of the HBPA-EP / D-230 system is significantly higher than that of the HBPA-EP / T-403 system. This is because the three amine groups in the HBPA-EP / T-403 system are all active groups, and the network structure generated by the reaction makes it more stable; and as the crosslinking density increases, the space between the crosslinking points is further reduced, resulting in a gradual decrease in the flexibility of the molecular chain segments. When impacted, the impact performance is reduced due to insufficient segment flexibility. The impact strength of the HBPA-EP / MeTHPA system is greater than that of the E-51 / MeTHPA system, mainly because there are no rigid groups in the hydrogenated bisphenol A epoxy resin, which enhances its flexibility and thus increases its impact strength.
[0075] See also Figure 4 , the flexural strength of epoxy resin-based adhesives under different systems was analyzed. The flexural strength of the HBPA-EP / D-230 and HBPA-EP / T-403 systems is not very high. The flexural strength of the HBPA-EP / MeTHPA system is also higher than that of the E-51 / MeTHPA system because the reinforcing materials and coupling agents added during the preparation of the resin play a role in improving the mechanical properties.
[0076] See Table 1 for the test results of heat resistance and salt spray aging resistance of the composite material obtained by winding molding. After being placed in a damp heat aging box for 10 days, the composite material plate obtained by winding molding has a strength decrease of about 0.95% compared with being placed at room temperature for 10 days. After being placed in a salt spray aging box for 10 days, the strength has decreased by about 0.41% compared with being placed at room temperature for 10 days. The influence of damp heat environment on glass fiber reinforced composite materials is mainly achieved in two aspects. The first is the destruction of chemical bonds in the composite material, the penetration of water molecules, and the destruction of the resin matrix. Therefore, after the fiber is stressed, the transfer effect of the matrix is reduced, and the strength of the composite material decreases. The second is to achieve this by weakening the physical adsorption strength of the composite material, such as causing the composite material to foam and degumming, and finally aging and failure. For salt spray aging, during the salt spray corrosion process, firstly, part of the resin matrix dissolves into the salt spray, causing the matrix to change. Secondly, the different expansion coefficients of the fiber and resin in the composite material will cause a stress difference between the resin and fiber interface. If the stress difference is too large, cracks will appear on the outside of the composite material. Finally, when the stress exceeds the bonding force between the resin and the fiber, the cracks will expand and even cause the material to break. From the above two sets of data, it can be seen that the effects of wet heat aging and salt spray aging on the composite material sheet obtained by pultrusion are particularly small.
[0077] Table 1 shows the heat resistance and salt spray aging resistance of the wound epoxy glass cloth
[0078]
[0079] The experimental results show that the preparation method of the epoxy resin adhesive proposed in the present invention and the application of the epoxy resin adhesive in the repair of glass pipes, the prepared composite material has excellent mechanical properties, good corrosion resistance, aging resistance and processability, etc., and has very important social significance and economic benefits.
[0080] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.
Claims
1. An epoxy resin-based adhesive, characterized in that: In parts by mass, it includes the following components: 1 part of hydrogenated bisphenol A epoxy resin, 0.01-0.07 parts of reinforcing material, 0.02-0.07 parts of coupling agent, 0.35-0.51 parts of curing agent, and 0.01-0.06 parts of accelerator.
2. An epoxy resin-based adhesive according to claim 1, characterized in that: The curing agent is polyetheramine D-230, T-403 or MeTHPA.
3. The epoxy resin-based adhesive according to claim 1, characterized in that: The accelerator is benzyldimethylamine or 1,8-diazabicycloundec-7-ene.
4. The epoxy resin-based adhesive according to claim 1, characterized in that: The reinforcing material is magnesium aluminum carbonate type layered double hydroxide Mg / Al-LDHs.
5. The epoxy resin-based adhesive according to claim 1, characterized in that: The coupling agent is γ-(2,3-epoxypropoxy)propyltrimethoxysilane KH-560.
6. The method for preparing the epoxy resin-based adhesive according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) mixing the dried hydrogenated bisphenol A epoxy resin with a reinforcing material, a coupling agent, etc. in a uniform proportion to obtain a component A; (2) dispersing component A, then mixing it evenly with a curing agent and an accelerator, ultrasonically treating it, and then vacuuming it to obtain a hydrogenated bisphenol A epoxy resin matrix; (3) dispersing a hydrogenated bisphenol A epoxy resin matrix, performing ultrasonic treatment, vacuum drying, evacuating, and curing to obtain an epoxy resin-based adhesive.
7. The method for preparing the epoxy resin-based adhesive according to claim 6, characterized in that: In step (2), the dispersion is carried out for 5-10 minutes and the ultrasonic treatment is carried out for 15-30 minutes.
8. The method for preparing the epoxy resin-based adhesive according to claim 6, characterized in that: In step (2), vacuum is applied at 0.01 MPa.
9. The method for preparing the epoxy resin-based adhesive according to claim 6, characterized in that: In step (3), the dispersion is carried out for 5-10 minutes and the ultrasonic treatment is carried out for 15-30 minutes.
10. Use of the epoxy resin-based adhesive according to any one of claims 1 to 5 as a repairing agent in repairing glass fiber reinforced plastic pipes.